Geomechanical characterization of an Italian complex formation with a block-in-matrix fabric. Issue 1 (August 2021) - Napoli, M L; Barbero, M; Scavia, C
Abstract: Melanges are chaotic and heterogeneous geological mixtures of strong rock blocks embedded in a weaker finer-grained matrix. These complex formations, often referred to as "bimrocks" (block-in-matrix rocks) and "bimsoils" (block-in-matrix soils), are characterized by a high spatial, dimensional and lithological variability. Such a variability, together with the presence of rock inclusions of different lithologies and dimensions, makes the collection of representative high-quality specimens for laboratory tests very challenging. As a consequence, the determination of the geomechanical properties of such geomaterials is extraordinarily problematic. In this paper a preliminary characterization of an Italian sedimentary chaotic melange is performed by means of several laboratory tests. In dry conditions it looks like a bimrock but it is very sensitive to water and will transform into a bimsoil if it comes into contact with water. Since conventional drilling methods could not be employed to collect the specimens, a manual coring had to be used. The irregular lumps obtained were then cut with a specially made cutting machine. Point load tests and uniaxial compression tests were performed on the melange specimens. Atterberg limits, grading curves and mineralogical analyses were further carried out on the matrix material, in order to characterize it. The paper comments on both the procedure of these tests and the results obtained.